Natural graphite tailing-based composite material as well as preparation method and application thereof

Through oxidation treatment and liquid polyacrylonitrile coating technology, a high tap density natural graphite tail material is formed, which solves the problems of waste of natural graphite tail material resources and low electrochemical performance of batteries, and achieves improved performance and cost reduction of lithium-ion batteries.

CN119517945APending Publication Date: 2025-02-25SHENZHEN EIGEN EQUATION GRAPHENE TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311068468.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-24
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The prior art is difficult to effectively utilize natural graphite tail materials, resulting in waste of resources and high cost of lithium-ion battery materials. At the same time, the ultra-high surface area of ​​natural graphite makes it difficult for traditional carbon coating to achieve high tap density, reducing the electrochemical performance of the battery.

Method used

The natural graphite tail material is treated by oxidation to form a base material, mixed with liquid polyacrylonitrile and water, spray-drying, pre-oxidizing and sintering, forming a natural graphite tail material. This method repairs graphite structural defects through an amorphous carbon layer, constructs an isotropic structure, promotes the rapid diffusion of Li+ and optimizes the side reaction between the electrode and the electrolyte.

Benefits of technology

The composite material with high tap density has been achieved, which significantly improves the electrochemical performance of lithium-ion batteries, including higher discharge capacity, Coulomb efficiency and cycle life, and reduces material costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119517945A_ABST
    Figure CN119517945A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of lithium ion batteries, and particularly relates to a natural graphite tailing-based composite material as well as a preparation method and application thereof. According to the preparation method, the natural graphite tailings are wrapped by liquid polyacrylonitrile, then amorphous carbon layers are formed on the pores and the surface of the natural graphite tailings through sintering, the structural defects of the natural graphite tailings are repaired through the amorphous carbon layers, an isotropic structure is constructed, rapid diffusion of Li < + > is promoted, and anisotropy of a Li < + > diffusion path is weakened; and meanwhile, the side reaction of the electrode and the electrolyte is optimized, a uniform, complete and compact SEI film is formed on the surface of the electrode during charging and discharging, and the generation of lithium metal dendrites is inhibited, so that the electrochemical performance of the lithium ion battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium ion batteries, and in particular relates to a natural graphite tailings-based composite material and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries, which feature high capacity, high energy density, low memory effect and slow self-discharge, have developed rapidly in the past few decades and will bring greater social demand given the increasing demand for electric vehicles and renewable energy storage.

[0003] Graphite anode has high capacity (372 mAh g -1 ), low operating voltage (compared with Li / Li + Compared with about 0.1V) and long cycle life, it is still the main choice for commercial lithium-ion batteries, and its demand will increase significantly with the development of lithium-ion batteries. Due to limited resources and low production capacity, the material cost of lithium-ion batteries is relatively high.

[0004] Natural graphite mined from the earth's crust has defects and is large in size, so it cannot be used directly and needs to go through processes such as crushing, granulation, cleaning, graphitization, and particle screening. However, in these processes, especially the granulation process, there is a large amount of tailing waste, which is usually thrown away directly, causing resource waste and environmental burden. Therefore, the reuse of natural graphite tailings is conducive to easing the pressure on the graphite market and reducing the material cost of lithium-ion batteries.

[0005] Carbon coating is an effective way to improve the electrochemical performance of graphite anode. It can inhibit the side reaction with electrolyte, promote the formation of dense solid electrolyte interface (SEI) on the graphite surface, and achieve excellent cycle and rate performance. However, for natural graphite, due to its ultra-high surface area, traditional carbon coating is difficult to obtain graphite anode material with high tap density, which will reduce the electrochemical performance of the battery. Summary of the invention

[0006] The purpose of the present invention is to provide a natural graphite tailings-based composite material and a preparation method and application thereof. The method provided by the present invention can obtain a composite material with a high tap density, which can be applied to lithium ion batteries to further improve the electrochemical performance of lithium ion batteries.

[0007] In order to achieve the above object, the present invention provides the following technical solutions:

[0008] The present invention provides a method for preparing a natural graphite tailings-based composite material, comprising the following steps:

[0009] The natural graphite tailings are oxidized to obtain a base material;

[0010] The base material is mixed with liquid polyacrylonitrile and water, the obtained slurry is spray-dried, and then pre-oxidized and sintered in sequence to obtain the natural graphite tail material-based composite material.

[0011] Preferably, the particle size of the natural graphite tailings is 1 to 8 μm.

[0012] Preferably, the temperature of the oxidation treatment is 200-500° C., and the insulation time is 2-10 hours.

[0013] Preferably, the mass of the liquid polyacrylonitrile is 2 to 20% of the mass of the base material;

[0014] The solid content of the slurry is 30-40%.

[0015] Preferably, the mixing is carried out under stirring, and the stirring time is 2 to 5 hours.

[0016] Preferably, the spray drying temperature is 150-200°C.

[0017] Preferably, the pre-oxidation temperature is 180-250° C., and the holding time is 1-6 hours.

[0018] Preferably, the sintering temperature is 1000-1500°C, and the holding time is 2-6h;

[0019] The sintering is carried out under a protective atmosphere.

[0020] The present invention also provides a natural graphite tailings-based composite material prepared by the preparation method described in the above technical solution, comprising natural graphite tailings and amorphous carbon distributed on the surface and in the pores of the natural graphite tailings.

[0021] The present invention also provides the use of the natural graphite tailings-based composite material described in the above technical solution as a negative electrode material in a lithium ion battery.

[0022] The present invention provides a method for preparing a composite material based on natural graphite tailings, comprising the following steps: subjecting natural graphite tailings to oxidation treatment to obtain a base material; mixing the base material with liquid polyacrylonitrile and water, spray drying the obtained slurry, and then sequentially performing pre-oxidation and sintering to obtain the composite material based on natural graphite tailings. The present invention uses liquid polyacrylonitrile to wrap the natural graphite tailings, and then forms an amorphous carbon layer on the pores and surface of the natural graphite tailings through sintering, repairing the structural defects of the natural graphite tailings through the amorphous carbon layer, constructing an isotropic structure, and promoting Li + The rapid diffusion of Li +The anisotropy of the diffusion path; at the same time, the side reactions between the electrode and the electrolyte are optimized, and a uniform, complete and dense SEI film is formed on the electrode surface during charging and discharging, which inhibits the generation of lithium metal dendrites and thus improves the electrochemical performance of lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 A schematic diagram of the synthesis of the preparation method provided by the present invention;

[0024] Figure 2 The graphs are the test results of specific surface area and tap density of the natural graphite tailings-based composite materials and natural graphite tailings (NGT) obtained in Examples 1 to 3;

[0025] Figure 3 The SEM and TEM images of the natural graphite tailings-based composite material (NGT@LPAN) and natural graphite tailings (NGT) obtained in Example 2;

[0026] Figure 4 XRD and Raman diagrams of the natural graphite tailings-based composite material (NGT@LPAN) and natural graphite tailings (NGT) obtained in Example 2;

[0027] Figure 5 The first charge and discharge curves of the natural graphite tail material-based composite material obtained in Examples 1 to 3 and the battery assembled with natural graphite tail material;

[0028] Figure 6 The cycle performance curve of the NMC532 full battery assembled from the natural graphite tail material-based composite material (NGT@LPAN) obtained in Example 2 and the natural graphite tail material (NGT) at a voltage of 2.7 to 4.25 V and a current density of 0.33 C;

[0029] Figure 7 The cycle performance curve of the NMC532 full battery assembled from the natural graphite tail material-based composite material (NGT@LPAN) obtained in Example 2 and the natural graphite tail material (NGT) at a voltage of 2.7 to 4.25 V and a current density of 0.1 C;

[0030] Figure 8 The charge and discharge curves of the NMC532 full battery assembled from the natural graphite tail material-based composite material (NGT@LPAN) obtained in Example 2 and the natural graphite tail material (NGT) at 1C;

[0031] Fig. 9 The cycle performance curve of the NMC532 full battery assembled from the natural graphite tail material-based composite material (NGT@LPAN) obtained in Example 2 and the natural graphite tail material (NGT) at a voltage of 2.7 to 4.45 V and a current density of 0.33 C;

[0032] Fig.10 The SEM and TEM images of the negative electrode of the NMC532 full battery assembled from the natural graphite tail material-based composite material (NGT@LPAN) and natural graphite tail material (NGT) obtained in Example 2 after 60 cycles at a cut-off voltage of 4.45V;

[0033] Fig.11 The surface element percentage diagram of the negative electrode of the NMC532 full battery assembled from the natural graphite tail material-based composite material (NGT@LPAN) obtained in Example 2 and the natural graphite tail material (NGT) after 60 cycles at a cut-off voltage of 4.45V;

[0034] Fig.12 The C1s graph of the negative electrode of the NMC532 full battery assembled from the natural graphite tail material-based composite material (NGT@LPAN) and natural graphite tail material (NGT) obtained in Example 2 after 60 cycles at a cut-off voltage of 4.45V;

[0035] Fig.13 The O1s graph of the negative electrode of the NMC532 full battery assembled from the natural graphite tail material-based composite material (NGT@LPAN) obtained in Example 2 and the natural graphite tail material (NGT) after 60 cycles at a cut-off voltage of 4.45V;

[0036] Fig.14 The F1s graph of the negative electrode of the NMC532 full battery assembled from the natural graphite tail material-based composite material (NGT@LPAN) obtained in Example 2 and the natural graphite tail material (NGT) after 60 cycles at a cut-off voltage of 4.45V;

[0037] Fig.15 P2p diagram of the negative electrode of the NMC532 full battery assembled from the natural graphite tail-based composite material (NGT@LPAN) obtained in Example 2 and natural graphite tail (NGT) after 60 cycles at a cut-off voltage of 4.45V. DETAILED DESCRIPTION

[0038] The present invention provides a method for preparing a natural graphite tailings-based composite material, comprising the following steps:

[0039] The natural graphite tailings are oxidized to obtain a base material;

[0040] The base material is mixed with liquid polyacrylonitrile and water, the obtained slurry is spray-dried, and then pre-oxidized and sintered in sequence to obtain the natural graphite tail material-based composite material.

[0041] In the present invention, unless otherwise specified, all preparation raw materials are commercially available products well known to those skilled in the art.

[0042] The invention carries out oxidation treatment on natural graphite tailings to obtain base material.

[0043] In the present invention, the particle size of the natural graphite tailings is preferably 1 to 8 μm, more preferably 2 to 6 μm, and more preferably 3 to 5 μm. In the present invention, when the particle size of the natural graphite tailings is not within the above range, the natural graphite tailings are preferably pulverized by a jet mill, and the speed of the jet mill is preferably 5 r / s.

[0044] In the present invention, the temperature of the oxidation treatment is preferably 200-500°C, more preferably 300-450°C, more preferably 350-400°C; the holding time is preferably 2-10h, more preferably 4-8h, more preferably 5-6h. In the present invention, the amorphous carbon and defects in the natural graphite tailing particles can be removed by oxidation treatment.

[0045] After obtaining the base material, the present invention mixes the base material with liquid polyacrylonitrile and water, spray-dries the obtained slurry, and then sequentially performs pre-oxidation and sintering to obtain the natural graphite tail material-based composite material.

[0046] In the present invention, the liquid polyacrylonitrile is preferably a copolymer of acrylonitrile and acrylic acid, and the molar ratio of acrylonitrile to acrylic acid is preferably 20:1; the relative molecular mass of the liquid polyacrylonitrile is preferably 5000-20000.

[0047] In the present invention, the mass of the liquid polyacrylonitrile is preferably 2-20% of the mass of the base material, more preferably 5-18%, and more preferably 10-15%; the solid content of the slurry is preferably 30-40%, and more preferably 35%.

[0048] In the present invention, the mixing is preferably carried out under stirring conditions, and the stirring time is preferably 2 to 5 hours, more preferably 3 to 4 hours. The present invention does not specifically limit the stirring speed, as long as the raw materials can be mixed evenly.

[0049] In the present invention, the spray drying temperature is preferably 150 to 200° C., and more preferably 160 to 180° C. The present invention has no particular limitation on the spray drying process, and any method known to those skilled in the art may be used.

[0050] In the present invention, the pre-oxidation temperature is preferably 180-250°C, more preferably 200-230°C, more preferably 210-220°C; the holding time is preferably 1-6h, more preferably 2-5h, more preferably 3-4h. In the present invention, the pre-oxidation is preferably carried out in a muffle furnace.

[0051] In the present invention, the sintering temperature is preferably 1000-1500°C, more preferably 1200-1400°C, and more preferably 1250-1300°C; the holding time is preferably 2-6h, and more preferably 3-4h; the sintering is preferably carried out under a protective atmosphere, and the protective atmosphere is preferably argon.

[0052] The synthesis schematic diagram of the preparation method provided by the present invention is as follows Figure 1 shown.

[0053] The present invention also provides a natural graphite tailings-based composite material prepared by the preparation method described in the above technical solution, comprising natural graphite tailings and amorphous carbon distributed on the surface and in the pores of the natural graphite tailings. In the present invention, the thickness of the amorphous carbon is preferably 1 to 2 nm.

[0054] The present invention also provides the use of the natural graphite tailings-based composite material described in the above technical solution as a negative electrode material in a lithium ion battery.

[0055] To further illustrate the present invention, a natural graphite tailings-based composite material provided by the present invention, a preparation method thereof and applications thereof are described in detail below in conjunction with the accompanying drawings and embodiments, but they should not be construed as limiting the scope of protection of the present invention.

[0056] Example 1

[0057] The natural graphite tailings with a particle size of 1 to 8 μm are oxidized at 350° C. and kept warm for 6 hours to obtain a base material;

[0058] 500 g of base material, 35 g of liquid polyacrylonitrile (wherein the molar ratio of acrylonitrile to acrylic acid is 20:1 and the relative molecular mass is 18000) and 1000 g of water are mixed, and the obtained slurry is spray-dried at 180° C.; the dried material is placed in a muffle furnace, pre-oxidized at 220° C. for 3 hours, and then sintered at a nitrogen atmosphere at a temperature of 1250° C. for 4 hours to obtain the natural graphite tail material-based composite material (denoted as NGT@LPAN-7%).

[0059] Example 2

[0060] The natural graphite tailings with a particle size of 1 to 8 μm are oxidized at 350° C. and kept warm for 6 hours to obtain a base material;

[0061] 500 g of base material, 50 g of liquid polyacrylonitrile (wherein the molar ratio of acrylonitrile to acrylic acid is 20:1 and the relative molecular mass is 18000) and 1000 g of water are mixed, and the obtained slurry is spray-dried at 180° C.; the dried material is placed in a muffle furnace, pre-oxidized at 220° C. for 3 h, and then sintered at 1250° C. in a nitrogen atmosphere for 4 h to obtain the natural graphite tail material-based composite material (denoted as NGT@LPAN-10%).

[0062] Example 3

[0063] The natural graphite tailings with a particle size of 1 to 8 μm are oxidized at 350° C. and kept warm for 6 hours to obtain a base material;

[0064] 500 g of base material, 75 g of liquid polyacrylonitrile (wherein the molar ratio of acrylonitrile to acrylic acid is 20:1 and the relative molecular mass is 18000) and 1000 g of water are mixed, and the obtained slurry is spray-dried at 180° C.; the dried material is placed in a muffle furnace, pre-oxidized at 220° C. for 3 h, and then sintered at a nitrogen atmosphere at a temperature of 1250° C. for 4 h to obtain the natural graphite tail material-based composite material (denoted as NGT@LPAN-15%).

[0065] Performance Testing

[0066] Test Example 1

[0067] The specific surface area and tap density of the natural graphite tailings-based composite materials and natural graphite tailings (NGT) obtained in Examples 1 to 3 were tested, and the test curves obtained are as follows: Figure 2 As shown;

[0068] from Figure 2 It can be seen that with the increase of LPAN dosage, the specific surface area of ​​the sample decreases, while the tap density increases, indicating that the addition of LPAN helps to optimize the microstructural characteristics of NGT, thereby greatly improving the electrochemical performance.

[0069] Test Example 2

[0070] Figure 3 The SEM and TEM images of the natural graphite tailings-based composite material (represented by NGT@LPAN in the figure) and the natural graphite tailings (NGT) obtained in Example 2;

[0071] from Figure 3From the SEM image, it can be seen that the original NGT has a monodisperse flake morphology with a size of several microns, while NGT@LPAN mainly has a dense spherical particle morphology (~5μm) and contains some graphite fragments; a small amount of graphite fragments is beneficial to improve the compaction density of the electrode. Further TEM images show that there are a large number of defects in the NGT structure, and the defects almost disappear after carbon coating. In addition, compared with NGT, a thin carbon layer with a thickness of 1 to 2nm appears on the graphite surface of NGT@LPAN. The surface carbon layer can passivate the active surface of the graphite and prevent the graphite layer from being embedded in Li together with the organic solvent during the discharge process. + ions and reduce the decomposition of the electrolyte, forming the SEI film more effectively, thereby showing a higher first coulombic efficiency and gram capacity, and also improving the cycle performance.

[0072] Test Example 3

[0073] Figure 4 XRD and Raman diagrams of the natural graphite tailings-based composite material (represented by NGT@LPAN in the figure) and natural graphite tailings (NGT) obtained in Example 2;

[0074] from Figure 4 It can be seen that the layered structure (PDF#41-1487), crystallinity and degree of graphitization of graphite are almost unchanged after carbon coating. In general, there are a large number of structural gaps and defects in NGT, which exposes a larger active graphite surface to the electrolyte and produces more side reactions. After carbon coating modification, these pores and defects disappear, which can be reflected by the reduction of the surface area of ​​NGT@LPAN, indicating that LPAN can not only modify the graphite surface, but also penetrate into the graphite interior to fill the pores and defects during the carbonization process.

[0075] Test Example 4

[0076] The natural graphite tailings-based composite materials and natural graphite tailings (NGT) obtained in Examples 1 to 3 were respectively used as active materials to assemble button-type batteries;

[0077] The preparation method of the negative electrode is as follows: the active material, binder (styrene-butadiene rubber, SBR), thickener (sodium carboxymethyl cellulose, CMC) and conductive agent (Super P) are weighed and ground and mixed evenly in a ratio of 100:2.5:1.5:1, and then placed in a stirring and degassing box, and then an appropriate amount of deionized water is added, and then sealed and placed in an A-310 stirring and degassing machine and stirred at a rate of 2000r / min for 20min, and then the slurry is evenly coated on the surface of the copper foil, and dried in a vacuum drying oven at 70°C for more than 10h; the dried copper foil is cut into discs with a diameter of 14mm to obtain the electrode sheet required for the test;

[0078] The button cell assembly process is as follows: the obtained electrode sheet is used as the negative electrode, the lithium sheet with a diameter of 15.4 mm is used as the counter electrode, the diaphragm is a porous polypropylene diaphragm, the electrolyte on both sides of the diaphragm (the solvent of the electrolyte is DMC / EMC / EC (v / v / v=70:5:25), and the lithium salt is 1.5 mol / L LiPF6) is 40 μL, the button cell is assembled in a glove box with an argon atmosphere, and is left to stand for more than 18 hours before being formed, and the electrochemical performance of the obtained battery is tested;

[0079] The first charge and discharge curves obtained are as follows Figure 5 As shown, from Figure 5 It can be seen that NGT@LPAN-10% has a higher discharge capacity (400.33mAh / g) and coulombic efficiency (92.07%). The capacity and coulombic efficiency of NGT, NGT@LPAN-7% and NGT@LPAN-15% are 403.17mAh / g, 394.94mAh / g, 388.93mAh / g and 89.05%, 91.63%, 92.16%, respectively. Although the original NGT has the highest first discharge capacity, reaching 403.17mAh / g, the corresponding first coulombic efficiency is the lowest (89.05%), indicating that due to the large surface area and structural defects of NGT, there are more side reactions with the electrolyte, so it has a larger irreversible capacity.

[0080] Test Example 5

[0081] The natural graphite tailings-based composite material (represented by NGT@LPAN) obtained in Example 2 and natural graphite tailings (NGT) were used as negative electrode materials to assemble an NMC532 full battery;

[0082] An electrode sheet was obtained according to the preparation method of the negative electrode in Test Example 4;

[0083] The assembly process of the battery is as follows: the obtained electrode sheet is used as the negative electrode of the battery, the commercial NMC532 is used as the positive electrode of the battery, the diaphragm is a porous polypropylene diaphragm, the electrolyte on both sides of the diaphragm (the solvent of the electrolyte is DMC / EMC / EC (v / v / v=70:5:25), and the lithium salt is 1.5 mol / L LiPF6) is 40 μL, the button battery is assembled in a glove box with an argon atmosphere, and it is left to stand for more than 18 hours before being formed, and the electrochemical performance of the obtained full battery is tested:

[0084] (1) The test process is: the test voltage is 2.7~4.25V, the current density is 0.33C, and the cycle is 100 times. The cycle performance curve is as follows Figure 6 As shown;

[0085] from Figure 6It can be seen that the NGT@LPAN battery has a good cycle life with no capacity loss and a maximum capacity of 150.1 mAh / g, which is much better than the NGT battery with a capacity loss of 144.9 mAh / g to 125.8 mAh / g (capacity retention rate of 86.82%).

[0086] (2) When the test voltage is 2.7-4.25V, the current density is 0.1C, and the cycle is 500 times, the cycle performance curve is as follows Figure 7 As shown;

[0087] from Figure 7 It can be seen that when the rate is further increased to 1C and cycled 500 times, the cycle life of NGT@LPAN is also better than that of NGT, with a capacity retention rate of 84.32% (from 129.5 mAh / g to 109.2 mAh / g), while the capacity retention rate of NGT is 73.65% (from 124.5 mAh / g to 91.7 mAh / g).

[0088] The charge and discharge curves at a current density of 1C are as follows Figure 8 As shown, from Figure 8 It can be seen that the comparison of the charge and discharge curves of the 25th, 50th, 100th, 250th and 500th times also confirms that the improvement of the charge and discharge capacity of the composite material obtained by the present invention is significant. The improvement of the cycle performance of NGT@LPAN relative to NGT is closely related to the carbon modification of the graphite surface and the repair of internal defects, which makes the material compatible with the electrolyte and forms a uniform and dense SEI film on the active surface, preventing the co-embedding of solvated lithium ions and the solvent reduction stripping of the structural layer and the generation of gas. In addition, a complete and dense carbon layer is formed on the surface and filled in the gap, which can buffer the Li + The key role of the expansion and contraction of the graphite layer structure caused by intercalation makes the structure of the primary graphite particles more stable, thereby improving the cycle performance.

[0089] (3) In order to further study the deep charge and discharge capability of the material, a full cell assembled from Example 2 (represented by NGT@LPAN in the figure) and natural graphite tail (NGT) was tested with a higher cutoff voltage. The test conditions were: the test voltage drop was 2.7 to 4.45 V and the current density was 0.33 C.

[0090] The cycle performance curve obtained is as follows: Fig. 9 As shown, from Fig. 9 It can be seen that NGT@LPAN outperforms NGT in both capacity and cycle stability.

[0091] (5) For the test with a cut-off voltage of 4.45 V, the battery containing NGT and NGT@LPAN that had been cycled 60 times was disassembled and the negative electrode was characterized. The SEM and TEM images obtained are shown in Figure 2. Fig.10 As shown, it can be seen that there is a large area of ​​gray matter on the surface of the NGT electrode, while this substance is not detected on the NGT@LPAN electrode. The gray matter can be interpreted as the deposition of metallic lithium, which has a great impact on the capacity decay and even safety issues of the battery. It can be seen that the carbon layer modified NGT helps to inhibit the formation of lithium metal dendrites. There may be two reasons for this result: one is the weakening of anisotropy after granulation, and the other is the enhancement of the SEI film. The SEI film was further characterized by comparison. It can be seen that the SEI film formed on NGT@LPAN is dense, uniform, and continuous, with a typical thickness of 5nm, while the SEI film formed on the NGT particles is discontinuous (part of the graphite is almost exposed to the electrolyte). Completely coating the SEI film on the NGT surface can passivate the active surface of the graphite, prevent the continuous decomposition of the electrolyte during the cycle to produce side reactions, and thus improve the capacity retention rate.

[0092] (5) The negative electrode obtained by disassembling in (4) is subjected to XPS test, and the test results are as follows: Figures 11 to 15 As shown, Fig.11 is the surface element percentage diagram, Fig.12 is the C1s graph, Fig.13 is the O1s diagram, Fig.14 For F1s, Fig.15 It is a P2p graph;

[0093] Generally speaking, the more the organic electrolyte decomposes, the higher the content of Li2CO3. Figures 11 to 15 It can be seen that according to the XPS analysis, the content of Li2CO3 in NGT fitted by the C1s spectrum is 2.70%, which is higher than 1.07% in NGT@LPAN. The content of Li2CO3 in the O1s spectrum also has a similar change trend, confirming that the side reaction between graphite and electrolyte is significantly inhibited after carbon modification.

[0094] LiF is another important component of SEI film. LiF-rich SEI film has the function of stabilizing structure and improving electrochemical performance. Contrary to the trend of Li2CO3 content, the LiF content in NGT (18.15%) is lower than that in NGT@LPAN (25.98%), indicating that a more stable SEI film is formed on the surface of NGT@LPAN.

[0095] P2p spectrum analysis shows that lithium hexafluorophosphate (LiPF x and Li x PO y F z) are basically the same in content. Due to the reconstruction of the interface and repair of defects after carbon modification, the reactivity of the NGT surface and defects with the organic electrolyte is suppressed, thus making the NGT@LPAN membrane components and dosage better. It can be seen that the carbon modifier generated after LPAN is wrapped on the NGT surface can not only aggregate graphite fragments for secondary granulation, improve the specific surface area and density, but also enhance the Li + The isotropic nature of ion diffusion also allows for modification and repair of defects on the NGT surface, optimizing electrolyte decomposition and forming a complete, highly stable SEI membrane with excellent electrochemical performance. Therefore, NGT can be recycled for waste reuse to reduce the material cost of commercial lithium-ion batteries.

[0096] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A method for preparing a natural graphite tailings-based composite material, characterized in that: The following steps are involved: The natural graphite tailings are oxidized to obtain a base material; The base material is mixed with liquid polyacrylonitrile and water, the obtained slurry is spray-dried, and then pre-oxidized and sintered in sequence to obtain the natural graphite tail material-based composite material.

2. The preparation method according to claim 1, characterized in that: The particle size of the natural graphite tailings is 1 to 8 μm.

3. The preparation method according to claim 1, characterized in that: The temperature of the oxidation treatment is 200-500° C., and the insulation time is 2-10 hours.

4. The preparation method according to claim 1, characterized in that: The mass of the liquid polyacrylonitrile is 2 to 20% of the mass of the base material; The solid content of the slurry is 30-40%.

5. The preparation method according to claim 1, characterized in that: The mixing is carried out under stirring conditions, and the stirring time is 2 to 5 hours.

6. The preparation method according to claim 1, characterized in that: The spray drying temperature is 150-200°C.

7. The preparation method according to claim 1, characterized in that: The pre-oxidation temperature is 180-250° C., and the heat preservation time is 1-6 hours.

8. The preparation method according to claim 1, characterized in that: The sintering temperature is 1000-1500°C and the holding time is 2-6h; The sintering is carried out under a protective atmosphere.

9. The natural graphite tailings-based composite material prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The invention comprises natural graphite tailings and amorphous carbon distributed on the surface and in the pores of the natural graphite tailings.

10. Use of the natural graphite tailings-based composite material according to claim 9 as a negative electrode material in a lithium ion battery.